Pelatihan Optimalisasi Sumber Daya pada Usaha Kecil dan Menengah Menggunakan Metode Simplek Serta POM-QM - Tirsa Nina Lina; Matheus Supriyanto Rumetna; Frenny Silvia Pormes; Wiesje Ferdinandus; Frety Matahelumual (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2022)
The Covid-19 pandemic is still hitting until now, this has caused unrest among the public, especially for Small and Medium Enterprises (SMEs). Many SME players have also felt the impact of this situation, one of which is Mrs. Marthina, whose address is at Moyo kilometer 13, Sorong City, West Papua Province. The problem faced by Mrs. Martina is optimizing the existing resources so that she gets a profit in the midst of the pandemic situation so that her business can continue to operate. In such a situation, steps are needed to increase profits. These steps must use a technique or method so that they have estimates in a more accurate calculation. One method that can be used is the Simplex method, for that the Community Service (PkM) team at Victory Sorong University offers a resource optimization training program by utilizing the simplex method and IT in the form of POM-QM software for windows version 5.3. The main objective of this PKM program is to share knowledge to help SMEs to innovate and maintain business activities.